Modeling the Synergy of Organizational Culture and Leadership for Enhancing Teacher Engagement - Rohmat T.Z; Sri Setyaningsih; Suhendra (Cita konsultindo, 2026)
Teachers’ Organizational Citizenship Behavior (OCB) represents extra-role behavior that is essential for enhancing school effectiveness and organizational sustainability, particularly in private vocational high schools facing increasing performance demands and institutional competition. This study aims to examine the effects of servant leadership, organizational culture, personality, and work motivation on teachers’ OCB, as well as to determine priority indicators for improvement using SITOREM analysis. A quantitative survey approach was employed involving private vocational high school teachers in West Jakarta. Data were analyzed using path analysis to investigate direct and indirect relationships among variables, and SITOREM analysis to classify indicators into priority areas for immediate improvement and indicators to be maintained or further developed. The results of the path analysis reveal that servant leadership and individual factors significantly influence teachers’ OCB. Furthermore, the SITOREM analysis identifies several priority indicators requiring immediate improvement, including good faith, tolerance, virtue, conscientiousness, willingness to listen, organizational norms, self-confidence, willingness, and emotional stability. Conversely, indicators such as empathy, mutual cooperation, responsibility, appreciation, humility, and openness to experience are categorized as strengths that should be sustained and enhanced. This study contributes to the development of organizational behavior and educational leadership theory and provides an evidence-based strategic framework for school leaders to systematically strengthen teachers’ OCB in vocational education settings.